Integration of Manganese Dioxide‐Based Nanomaterials for Biomedical Applications. Issue 1 (7th December 2022) - Sun, Yudong; Wang, Yifei; Liu, Yaqi; Wang, Huimin; Yang, Changying; Liu, Xiaoqing; Wang, Fuan
Abstract : Advancements in nanotechnology have promoted the rapid development of diverse nanosystems for biomedical applications. Manganese dioxide (MnO2 ) nanomaterials have attracted numerous attentions in the field of biosensing and cancer treatment due to their unique properties, such as simple fabrication procedures, broad optical absorption, and high oxidation and catalytic ability. Especially, the intelligent stimuli‐responsiveness of MnO2 nanomaterials to tumor microenvironment (TME) greatly improves their performance in tumor imaging and cancer therapy. In this review, the synthetic methods of different MnO2 nanostructures (nanoparticles, nanosheets, and nanoflowers) are first introduced, followed by the introduction of MnO2 nanomaterials for various biosensing applications based on their unique characteristics. Then, the recent achievements and progress of MnO2 nanomaterials for cancer treatment are comprehensively summarized with a focus on various therapeutic enhancements profiting from their disassembled ingredients under TME guidance. Finally, the current challenges and future perspectives of this promising research are discussed in the fields of biomedicine. Abstract : In the last two decades, MnO2 nanomaterials have attracted increasing attention in the field of bioanalysis, biosensing, bioimaging, and biomedicine due to their good biocompatibility, low cost, broad absorption, and strong oxidability. Different synthesis methods result in various structures and functions of MnO2 as well as different biomedical applications. This review summarizes the preparation, function, and application of MnO2 nanomaterials.